2013
DOI: 10.5194/hess-17-783-2013
|View full text |Cite
|
Sign up to set email alerts
|

CREST-Snow Field Experiment: analysis of snowpack properties using multi-frequency microwave remote sensing data

Abstract: Abstract. The CREST-Snow Analysis and Field Experiment (CREST-SAFE) was carried out during January-March 2011 at the research site of the National Weather Service office, Caribou, ME, USA. In this experiment dual-polarized microwave (37 and 89 GHz) observations were accompanied by detailed synchronous observations of meteorology and snowpack physical properties. The objective of this long-term field experiment was to improve understanding of the effect of changing snow characteristics (grain size, density, tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Generally, SNTHERM appeared to simulate all snowpack properties closer to the snow surface better than those closer to the snow-ground interface. Additional studies by Lakhankar et al [73] and Koivusalo and Heikinheimo [74] have also shown good agreement between various SNTHERM simulated snowpack properties and in situ observations. Lakhankar et al demonstrated high agreement between bulk snow density (R = 0.97) and average grain size (R = 0.96) SNTHERM simulations and CREST-SAFE in situ observations.…”
Section: Methodology and Materialsmentioning
confidence: 56%
See 1 more Smart Citation
“…Generally, SNTHERM appeared to simulate all snowpack properties closer to the snow surface better than those closer to the snow-ground interface. Additional studies by Lakhankar et al [73] and Koivusalo and Heikinheimo [74] have also shown good agreement between various SNTHERM simulated snowpack properties and in situ observations. Lakhankar et al demonstrated high agreement between bulk snow density (R = 0.97) and average grain size (R = 0.96) SNTHERM simulations and CREST-SAFE in situ observations.…”
Section: Methodology and Materialsmentioning
confidence: 56%
“…Additional calibration parameters (i.e., irreducible water content for snow (0.017), density of new snow (73 kg/m 3 ), density limit for compaction of snow (96 kg/m 3 ), and the viscosity coefficient for overburden compaction (6.9 × 10 5 kg·s/m 2 )) needed by SNTHERM to simulate the deposition scheme were established based on previous studies [48,57,65,66,67,72]. CREST-SAFE provides all of its meteorological data in an hourly time step via an automated routine [73], whereas the NWS provides precipitation data in 15-min time steps. Naturally, the NWS precipitation data was aggregated to hourly time intervals.…”
Section: Methodology and Materialsmentioning
confidence: 99%
“…It has to be pointed out that the snowmelt estimation is still not very precise, as the temperature index model is relatively simple (Garen and Marks, 2005;Herrero et al, 2009;Lakhankar et al, 2013). Also, we do not consider surface run-off due to the high permeability of surface deposits.…”
Section: Performance Of Modified Tank Model In Snowmelt Seasonmentioning
confidence: 99%
“…Thus, in our study the judgment of precipitation type still uses the widely used statistic model. For the snowmelt calculation we used empirical equations to make the process earlier, because sophisticated models which can calculate the snowmelt precisely are quite complex and require several physical parameters, including topography, precipitation, air temperature, wind speed and direction, humidity, downwelling short-wave and long-wave radiation, cloud cover and surface pressure (Garen and Marks, 2005;Herrero et al, 2009;Lakhankar et al, 2013). In addition, compared to the original tank model without considering the snowmelt, we emphasized the tank model coupling the function of snowmelt (we just choose the simple snowmelt module).…”
Section: Introductionmentioning
confidence: 99%
“…Such models are rather complex and require several physical parameters including (but not limited to) topography, precipitation, air temperature, wind speed and direction, humidity, downwelling shortwave and longwave radiation, cloud cover, surface pressure. The determination of accurate values of these parameters, and their variation in space and time, is only possible for very well-equipped experimental test sites (Lakhankar et al, 2013); therefore, simplified approaches as temperature-index methods are also widely used (Kustas et al, 1994;Rango and Martinec, 1995;Hock, 1999Hock, , 2003Jost et al, 2012). Those models use air temperature as an index to perform an empirical correlation with snowmelt and require only a few parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%